Implementing Smoke-Free Housing Policies Among Multiunit Housing Owners in New York City Between 2012 and 2015. (July 2019) - Debchoudhury, Indira; Farley, Shannon M
Smoke-free regulations are the norm in workplaces and public outdoor areas across New York City (NYC), and smoke-free apartment building regulations are less widespread. In 2017, more than one-third (37.6%) of NYC multiunit housing (MUH) residents reported breathing secondhand smoke (SHS) from neighboring units. In 2015, the NYC Health Department conducted a cross-sectional phone survey among a random sample of NYC low-income and market-rate MUH property owners/managers as a follow-up to a 2012 study. The study compared owners' experiences and attitudes regarding smoke-free policies. Bivariate and multivariable logistic regression analyses were used. Overall, the proportion of owners who have a policy prohibiting smoking in individual units (33% vs 37%) increased between 2012 and 2015. In both waves, owners without low-income units (wave 1: 36%, wave 2: 40%) were more likely to have smoke-free housing policies than those with low-income units (wave 1: 26%, wave 2: 30%). The models adjusted for factors such as current smoking, size and nature of housing units, and several beliefs. Owners in 2015 were more likely to have a smoke-free policy (adjusted odds ratio [AOR]: 1.25, 95% confidence interval (CI): 1.003, 1.564) and, among those without a current smoke-free policy, to have future interest in smoke-free unit policies (AOR: 1.68, 95% CI: 1.17, 2.39) than in 2012. An increasing proportion of NYC MUH owners are reducing tenant exposure to SHS and providing them with a healthier environment. We expect to see further expansion of smoke-free housing in NYC as positive norms grow.